Schadenfreude and life satisfaction: effect of anger and aggressiveness - Ilia, Iosif; Rad, Dana; Dughi, Tiberiu; Egerau, Anca; Demeter, Edgar; Rad, Gavril (Technium Social Sciences Journal, 2022)
Many individuals become aggressive in reaction to an actual or potential danger, or it can be a learned behaviour that assists them in meeting their needs. Anger is a natural emotion that everyone feels at different moments. It is, in effect, a normal reaction to a challenge, assisting us in preparing for defence or standing up for ourselves It usually occurs as a response to thoughts or feelings such as pain, irritation, worry, envy, discomfort, rejection, or shame. The purpose of this investigation is to examine effects of trait anger (AN) and aggressiveness (AG) on life satisfaction (LS) of general adult population, as well as to determine whether trait anger (AN) moderates the mediating effect of aggressiveness (AG) in the schadenfreude (SCH) – life satisfaction (LS) relationship. 390 individuals responded to an online investigation, selected via convenience sampling. Trait anger was found to moderate the effect of schadenfreude and life satisfaction. Increased levels of aggressiveness were linked to low levels of life satisfaction. Conditional effects found a stronger association between schadenfreude and aggressiveness for those low in trait anger relative to those high in trait anger. Participants with low scores in trait anger and high scores in schadenfreude had higher levels of aggressiveness than individuals with lows cores in trait anger. Conclusions and implications are discussed.